5. PENENTUAN KELAS RESIKO DIDARAT MENGGUNAKAN METODOLOGI SORA (SPECIFIC OPERATION RISK ASSEMENT) PADA APLIKASI DRONE PENYIRAMAN TOPXGUN - Much. F. Muchaddats; Kurniawan P.Y.; A. Syaefudin; Aditama T (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2024)
This study aims to determine how the operating system using UnmannedAircraft Systems (UAS) is subject to compliance with applicable regulations, technicalrequirements, and operational limitations. In order to obtain approval from the authorities,the Indonesian Aviation Safety Agency (DGCA) has stipulated in the current regulatoryframework that a safety risk assessment must be carried out for Drone operations in theSpecial category. Special Operational Risk Assessment (SORA) is a methodologydeveloped by JARUS (Joint Authority for Rulemaking on Unmanned Systems) to conductrisk assessments. The regulation is stated in PKPS (Civil Aviation Safety Regulation) 107.This paper presents the application of the SORA methodology for Drone wateringoperations developed in the Spraying Drone project by PT. XYZ. This project develops anautonomous system for Aerial Watering with a small Drone team. This paper discusses allsteps in SORA, evaluates operational risks, and discusses mitigation measures in thesystem. A positive evaluation was achieved for the proposed operation, which will facilitatetechnology transfer for the Spraying Drone system and its future integration into airspaceoperations.